Impact of interventions on mpox transmission during the 2022 outbreak in Canada: a mathematical modeling study of three different cities - Fanyu Xiu; Carla M. Doyle; Jorge Luis Flores Anato; Jesse Knight; Linwei Wang; Joseph Cox; Daniel Grace; Trevor A. Hart; Terri Zhang; Shayna Skakoon-Sparling; Milada Dvorakova; Rita Shahin; et al. (International Journal of Infectious Diseases)
Objectives: The global mpox (clade II) outbreak of 2022 primarily affected gay, bisexual, and other men who have sex with men (GBM) and was met with swift community and public health responses. We aimed to estimate the relative impact of changes in sexual behaviors, contact tracing/isolation, and first-dose vaccination on transmission in Canadian cities. Methods: We estimated changes in sexual behaviors during the outbreak using 2022 data from the Engage Cohort Study, which recruited self-identified GBM in Montréal, Toronto, and Vancouver (n = 1,445). We developed a transmission dynamic model to estimate the fraction of new infections averted due to the three interventions in each city. Results: The empirical estimates of sexual behavior changes were imprecise: a 20% reduction (RR = 0.80; 95% credible interval [95% CrI]: 0.47-1.36) in the number of sexual partners in the past 6 months among those reporting ≤7 partners and a 33% (RR = 0.67; 95% CrI: 0.31-1.43) reduction among those with >7 partners. The three interventions combined averted 46%-58% of cases. Reductions in sexual partners and contact tracing/isolation prevented approximately 12% and 14% of cases, respectively. Vaccination's effect varied across cities due to the programs' timing and coverage, with 21%-39% mpox infections prevented. Conclusions: Reduction in sexual activity, contact tracing/isolation, and vaccination all contributed to accelerating epidemic control. Early vaccination had the largest impact.